The Influence of Financial Inclusion, Financial Planning, and Financial Attitudes on the Financial Management of Culinary MSME Owners Lubuk Pakam - Andini, Ayu; Soemitra, Andri; Dharma, Budi (Yayasan Sinergi Kawula Muda, 2024)
Actively improving the economy and reducing unemployment in Indonesia is played by Micro, Small and Medium Enterprises. Financial management holds significance in business operations., including financial inclusion, financial planning, and financial attitudes to ensure optimal business financial management. This study aims to assess the impact of Financial Inclusion, Financial Planning, and Financial Attitudes on Financial Management. The goal of this research is to enhance understanding and become a basis for legislators and local governments to focus more on improving the financial management of MSME businesses. Using a quantitative approach, this research involved culinary MSME owners in Lubuk Pakam District as a population. Samples were taken using purposive sampling techniques and the Lemeshow formula to obtain 96 respondents. The data collected is original or first hand (primary) data. Various tests such as validity, reliability, multiple regression, normality, Kolmogorov-Smirnov, multicollinearity, heteroscedasticity, as well as F, t tests, and coefficient of determination were included in the data analysis. It is known that financial management of culinary MSME owners in Lubuk Pakam District is influenced positively and significantly by financial planning and financial attitudes, while financial inclusion does not show a significant influence. Overall, financial inclusion, financial planning and financial attitudes contributed 78.50% to financial management, meanwhile, the remaining 21.50% was attributed to factors or variables that were not included in this study. For future research, it is suggested to include additional independent variables and increase the sample size to achieve a more comprehensive insight into how other variables affect financial behavior.